“Scotomes” or “blind spots” in the medical field that limit its role in adolescent sexual and reproductive health (ASRH) : ideas about how to eliminate them (2014)
ABSTRACT: This article reviews the medical field’s role in adolescent sexual and reproductive health (ASRH) from the historical perspectives of two influential medical specialties: adolescent and young adult medicine and pediatric and adolescent gynecology. The article identifies aspects that act as blind spots, limiting the medical field’s capacity to respond to the challenges of ASRH. The article reviews the theoretical contributions of the critical social sciences, highlighting some of Latin America’s collective health movements and feminist theories, as well as the hegemonic medical institutional discourses and practices that perpetuate health inequities in relation to patients’ sexualities, subjectivities and identities. Finally, this paper presents a new concept: that of “sexual citizenship,” a useful concept that integrates these theoretical and methodological contributions into a relational analysis that includes sexualities, subjectivities and identities. The incorporation of these theoretical developments into medical training programs would generate a radical change in the role of the medical field that has been challenged by the new conceptual and ethical framework of the UN system, as confirmed at the conferences in Cairo (1994) and Beijing (1995). These conferences urged states to offer policies that guarantee sexual and reproductive rights (SRR).